Challenges faced by Teachers and Students during and in the aftermath of the transition to Online education - Sani, Saleh (ADA University, 2020)
Covid-19 pandemic has forced the sudden shift from the regular face-to-face education to online education. Never before has the world witnessed nor it has been prepared to such a detrimental impact to the educational system. ADA School, the client of this business consultancy project, closed the doors of its campus on 3rd of March, and as a matter of fact has not reopened them ever since. Starting from March 2020, ADA School continues to provide education in a remote, technology based way. The closure of ADA School was necessary for the protection of its students and employees, but it significantly disrupted the teaching and learning processes. In order to keep the education going, measures in response to covid-19 had to be implemented promptly, without sufficient time for planning. This study aimed at identifying the key challenges faced by students and teachers with the transition to online education during covid-19 at ADA School. he main purpose of the study was to investigate the phenomenon associated with the transition from the regular delivery of knowledge in the classroom setting to the online teaching mode. The selected qualitative design for this consultancy project is the general qualitative inquiry, with the use of in-depth semi-structured interviews and focus group discussions, out of which the lived experience of participants was possible to interpret. The quantitative part of the analysis was based on the data collected through the questionnaires. Multiple linear regression was applied in order to find the impact of independent variables on the dependent ones. Challenges identified by the study were grouped into key areas. Those include internet connectivity, access to digital devices, digital literacy, working environment at home, physical health, emotional well-being, assessment, student engagement and preparation, distractions during online classes, instructional time and online teaching skills.
Keywords: Business; Education, Online -- Azerbaijan.; School -- Azerbaijan.; Distance education -- Azerbaijan.